krissywatts
solve system of equation:
x+y=-1
y-z=4
2x+y+5z=-38
i need step by step help please?
Delete
Share
This Question is Closed
Kanwar245
Best Response
You've already chosen the best response.
1
step1; multiply equation 1 with -1
Kanwar245
Best Response
You've already chosen the best response.
1
step2; add equation 1 and equation 2
Kanwar245
Best Response
You've already chosen the best response.
1
you'll get an equation in terms of x and z
krissywatts
Best Response
You've already chosen the best response.
0
so my finale for that would be -x-z=4 correct?
krissywatts
Best Response
You've already chosen the best response.
0
@Kanwar245
Kanwar245
Best Response
You've already chosen the best response.
1
-x - z = 5
krissywatts
Best Response
You've already chosen the best response.
0
yes sorry
krissywatts
Best Response
You've already chosen the best response.
0
no what is the next step?
krissywatts
Best Response
You've already chosen the best response.
0
now*
Kanwar245
Best Response
You've already chosen the best response.
1
also you can rewrite last equation as
2x + 4 + z + 5z = -38
Kanwar245
Best Response
You've already chosen the best response.
1
2x + 6z = -42
or x + 2z = 31
Kanwar245
Best Response
You've already chosen the best response.
1
and you have -x -z = 5
Kanwar245
Best Response
You've already chosen the best response.
1
solve these two equations
krissywatts
Best Response
You've already chosen the best response.
0
okay
Kanwar245
Best Response
You've already chosen the best response.
1
you get z = 26
Kanwar245
Best Response
You've already chosen the best response.
1
x = -31
krissywatts
Best Response
You've already chosen the best response.
0
is y 30?
krissywatts
Best Response
You've already chosen the best response.
0
@Kanwar245
krissywatts
Best Response
You've already chosen the best response.
0
@campbell_st
krissywatts
Best Response
You've already chosen the best response.
0
@agent0smith
agent0smith
Best Response
You've already chosen the best response.
0
Assuming Kanwar245 is correct,
z = 26
x = -31
to find y, use these values in one of these equations to find y:
x+y=-1
y-z=4
2x+y+5z=-38
from the first, x+y=-1, so
\[\large y = -1 - x = -1 - (-31) = 30 \].
or use the second, y-z=4, so
\[\large y= 4+z = 4+26 = 30\]
or use the third, 2x+y+5z=-38, so
\[y = -38 -2x -5z = -38 -2(-31)-5(26) = -106\]
This doesn't agree with the other value for y of 30, so it's possible there's a mistake somewhere.